Awareness and Adoption of Technologies by Women Headed Households - K. Uma Rani,; K.Sai Maheswari, (Journal of Agricultural Extension Management, 2025)
This study examines the extent of participation of women heading the households, in agriculture and livestock activities and their awareness and adoption of related technologies. Results reveal that around 50 per cent of the sample women were not aware of the technologies. Some of the suggestions to improve awareness include, organizing location specific training based on the crops grown in the area; telecasting programmes to create awareness, choosing fields belonging to women heading the households for demonstrations and training under Farmers Field Schools to encourage their participation, and delegating women extension functionaries for providing extension advise and services to these women. Extension programmes, need to give special emphasis on the needs and problems of women heading the households and mainstream them into the developmental programmes.